Genetic Clues on Implantable Cardioverter-Defibrillator Placement in Young-Age Hypertrophic Cardiomyopathy: A Case Report of Novel MYH7 Mutation and Literature Review - Li, Xing; Tang, Jie; Li, Jinhui; Lin, Sha; Wang, Tao; Zhou, Kaiyu; Li, Yifei; Hua, Yimin (Frontiers in Cardiovascular Medicine, 2021)
Background: Hypertrophic cardiomyopathy (HCM) is the second most common cardiomyopathy in childhood with a life-threatening risk. Implantable cardioverter-defibrillator (ICD) placement is recommended for early prevention if there are two or more clinical risk factors. Pediatric patients with HCM are at a higher risk of sudden cardiac death (SCD), but there are limited reports on indications for ICD implantation in children. Herein we describe the case of Myh7 mutation-induced HCM and cardiac arrest in a patient and evaluated information originating from genetic background to guide ICD administration. Case Presentation: The patient was a girl aged 7 years and 8 months who had been diagnosed with cardiomyopathy in utero 8 years prior. She had had recurrent cardiac arrests within the last 4 years. Electrocardiography indicated abnormalities in conduction, and ST segment changes. Echocardiography indicated significant left ventricular hypertrophy and hypertrophic systolic interventricular septum. Cardiac magnetic resonance imaging depicted general heart enlargement with hypertrophy, and delayed enhancement in myocardium with perfusion defect was also evident. Whole exon sequencing identified a de novo c.2723T>C (p.L908P) heterozygous mutation in the MYH7 gene. MYH7 p.L908P predicted unstable protein structure and impaired function. The patient was scheduled for ICD implantation. There were no complications after ICD implantation, and she was discharged from hospital on the 10th day. Regular oral beta-blockers, amiodarone, spironolactone, and enalapril were administered, and she was required to attend hospital regularly for follow-up. During follow-up there were no cardiac arrests. Literature review of clinical prognoses associated with genetic mutations of MYH7, MYBPC3, TNNI3, TNNT2, and TPM1 in pediatric HCM patients with and without ICD implantation indicated that they were totally differently. Previous reports also indicated that gene mutations predicted earlier onset of cardiac hypertrophy, and increase likelihood of SCD. Conclusion: Variant burden and variant type contribute to the risk of adverse events in pediatric HCM. Early recognition and intervention are vital in children. Gene mutation could be considered an indication for early ICD placement during standard risk stratification of HCM patients. Whether this extends to the majority of pediatric patients requires further investigation.